Manual de adaptación de lentes oftálmicos verificación de parámetros ópticos en monturas oftálmicas (2021)
he objective of this manual is to achieve a tool that allows an adequate adaptation of ophthalmic lenses, allowing to follow the appropriate procedures to record and verify the main optical parameters and thus provide the patient with a quality adaptive process in harmony with their day-to-day life and their needs, hoping that the adaptation of ophthalmic lenses will not only correct the defect refraction of the patient but also provides quality of life, comfort and aesthetics.